Virtual reality to improve low-back pain and pelvic pain during pregnancy: a pilot RCT for a multicenter randomized controlled trial - García-López, Francisco-José; Pastora-Bernal, José-Manuel; Moreno-Morales, Noelia; Estebanez-Pérez, María-José; Liñán-González, Antonio; Martín-Valero, Rocío (Frontiers in Medicine, 2023)
A significant proportion of women experience low back and pelvic pain during and after pregnancy, which can negatively impact their daily lives. Various factors are attributed to these complaints, and many affected women do not receive adequate healthcare. However, there is evidence to support the use of different physiotherapeutic interventions to alleviate these conditions. Virtual reality is a promising complementary treatment to physiotherapy, particularly in improving pain perception and avoidance. The primary objective of this study is to evaluate the efficacy of a four-week program combining VR and physiotherapy compared to standard physiotherapy in pregnant women with low back and pelvic pain, in terms of improving pain avoidance, intensity, disability, and functional level. The study also aims to investigate patient satisfaction with the VR intervention. This research will be conducted through a multi-center randomized controlled clinical trial involving pregnant patients residing in the provinces of Seville and Malaga with a diagnosis of low back and pelvic pain during pregnancy. The alternative hypothesis is that the implementation of a Virtual Reality program in combination with standard physiotherapy will result in better clinical outcomes compared to the current standard intervention, which could lead to the development of new policies and interventions for these pathologies and their consequences. Clinical trial registration: clinicaltrials.gov, identifier NCT05571358.